Compromised white matter integrity in obesity. Issue 4 (10th February 2015) - Kullmann, S.; Schweizer, F.; Veit, R.; Fritsche, A.; Preissl, H.
Summary: Obesity is associated with both structural and functional changes of the central nervous system. While gray matter alterations in obesity point to a consistent reduction with increasing body mass index (BMI), volumetric changes in white matter are more complex and less conclusive. Hence, more recently, diffusion tensor imaging (DTI) has been employed as a highly sensitive tool to investigate microstructural changes in white matter structure. Parameters of diffusivity and anisotropy are used to evaluate white matter and fibre integrity as well as axonal and myelin degeneration. Fractional anisotropy (FA) is the most commonly used parameter as it is the best estimate of fibre integrity. The focus of this review was on the relationship between obesity and brain alterations assessed by DTI. Altogether, these studies have shown a loss of white matter integrity with obesity‐related factors, especially in tracts within the limbic system and those connecting the temporal and frontal lobe. More specifically, multiple studies found an inverse association between BMI and FA in the corpus callosum, fornix, cingulum and corona radiata in elderly and young adults as well as children. Furthermore, significant interactions were observed between BMI and age, pointing to accelerated ageing of white matter structure in obese.